(untitled) ([Inter]sections, 2025)
This article examines themes of mobility and identity Ladee Hubbard’s The Talented Ribkins (2017). I use the lens of mobility studies to closely analyze the novel’s two primary characters, Johnny and Eloise, and the ways in which their cross-Florida road trip is both a literal and symbolic journey to self-discovery for each. In addition, I look at W.E.B. Du Bois and Zora Neale Hurston as inspiration for Hubbard’s novel and explore the role of storytelling as central to each character’s process of identity formation. I furthermore consider the novel’s Florida setting as particularly fertile ground for interrogations of mobility, given the state’s place in the literary and national imaginations as a nexus of movement, ultimately asserting that reading The Talented Ribkins within this context can only illuminate its commentary on racial justice.